SEVEN IN ABSENTIA Ubiquitin Ligases Positively Regulate Defense Against Verticillium dahliae in Gossypium hirsutum - Ren, Zhongying; Liu, Wei; Wang, Xingxing; Chen, Mingjiang; Zhao, Junjie; Zhang, Fei; Feng, Hongjie; Liu, Ji; Yang, Daigang; Ma, Xiongfeng; Li, Wei (Frontiers in Plant Science, 2021)
Ubiquitination is a post-translational regulatory mechanism that controls a variety of biological processes in plants. The E3 ligases confer specificity by recognizing target proteins for ubiquitination. Here, we identified SEVEN IN ABSENTIA (SINA) ubiquitin ligases, which belong to the RING-type E3 ligase family, in upland cotton (Gossypium hirsutum). Twenty-four GhSINAs were characterized, and the expression levels of GhSINA7, GhSINA8 and GhSINA9 were upregulated at 24 h after inoculation with Verticillium dahliae. In vitro ubiquitination assays indicated that the three GhSINAs possessed E3 ubiquitin ligase activities. Transient expression in Nicotiana benthamiana leaves showed that they localized to the nucleus. And yeast two-hybrid screening revealed that they could interact with each other. The ectopic overexpression of GhSINA7, GhSINA8 and GhSINA9 independently in Arabidopsis thaliana resulted in increased tolerance to V. dahliae, while individual knockdowns of GhSINA7, GhSINA8 and GhSINA9 compromised cotton resistance to the pathogen. Thus, GhSINA7, GhSINA8 and GhSINA9 act as positive regulators of defense responses against V. dahliae in cotton plants.